Environmentalism and global international society - Falkner, Robert 1967- (Cambridge University Press, 2021)
Explains how environmentalism became a fundamental norm in international relations and explores the impact of the greening of international society
Keywords: Environmentalism / International cooperation / History; Environmental protection / International cooperation / History; International relations; Electronic books